IMF and World Bank sponsored structural adjustment programs in Africa : Ghana's experience, 1983-1999 - Konadu-Agyemang, Kwadwo; International Monetary Fund.; The World Bank. (Burlington, VT : Ashgate, 2001)
This text questions the benefits of Structural Adjustment Programmes (SAPs). The book seeks to appraise the impact of the World Bank and IMF programmes in Africa focusing on Ghana's 16-year experience.
Includes bibliographical references and index.
oif 21/07/2016
Loan
Keywords: Structural adjustment (Economic policy); Ghana